Indications of complex lithospheric structure around the Cheyenne Belt in the western U.S. based on shear wave splitting analysis - Millikan, Ronald, author; Schutt, Derek, advisor; Hannah, Judy, committee member; Breidt, Jay, committee member (Colorado State University. Libraries, 2014)
This study employs the method of shear wave splitting using a modified Silver and Chan methodology to produce constraints on the character of the upper mantle below the Cheyenne Belt suture zone (CB), North America. The CB marks the boundary between the Proterozoic Yavapai and Archean Wyoming Provinces. A previously undetected regional anisotropic fossil fabric with north trending fast axis orientations was detected in topographically low areas and interpreted produced by Proterozoic strain created during the convergence that produced the CB. Anisotropy results sub-parallel to absolute plate motion (APM) were detected in the mountainous areas. This is interpreted as caused by local post-Laramide heating of the lithosphere, which has reset Proterozoic anisotropy. This interpretation explains the complexity of shear wave splitting noted in Colorado by other studies.
Keywords: anisotropy; shear wave splitting; lithospheric structure; Cheyenne Belt